2018
DOI: 10.1186/s12917-018-1676-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Streptococcus agalactiae in a female llama (Lama glama) in South Tyrol (Italy)

Abstract: BackgroundStreptococcus agalactiae is pathogenic for both animals and humans. In dairy cattle it commonly causes mastitis, with great economic losses, and there is scientific evidence of mastitis, caseous lymphadenitis, contagious skin necrosis and purulent infections associated with S. agalactiae in camels (Camelus dromedarius) as well. In humans, it is a common component of the respiratory and gastrointestinal microflora, but it can also act as a pathogen, especially in elderly people and immunocompromised p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The correlation between mastitis and Streptococcus agalactiae is well-documented. It has been reported that Streptococcus agalactiae was isolated from a healthy or sub-clinically infected camels as well in the pre-milking cows heifers [5,12,14,20,21], isolated from lactating camels (Camelus dromedarius) with mastitis [22], and isolated from a female llama (Lama glama) with chronic suppurative subcutaneous infection [23].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between mastitis and Streptococcus agalactiae is well-documented. It has been reported that Streptococcus agalactiae was isolated from a healthy or sub-clinically infected camels as well in the pre-milking cows heifers [5,12,14,20,21], isolated from lactating camels (Camelus dromedarius) with mastitis [22], and isolated from a female llama (Lama glama) with chronic suppurative subcutaneous infection [23].…”
Section: Discussionmentioning
confidence: 99%
“…Some Streptococcus species have been also reported in South American camelids (alpacas (Vicugna pacos) and llamas (Lama glama)), e.g. S. pluranimalium [18], S. agalactiae [19], S. equi subsp. zooepidemicus [4,5], and S. bovis biotype I [7], the latter species has been reclassified in 2003 as Streptococcus gallolyticus subsp.…”
mentioning
confidence: 97%
“…To our best knowledge Streptococcus spp. of alpacas and California sea lions have not yet been well investigated and only a few reports have been published [4,5,7,[16][17][18][19]. In this study, we report the discovering of three novel Streptococcus species, which were isolated from faeces of alpacas (Vicugna pacos) and cattle (Bos taurus), and from respiratory tract of California sea lions (Zalophus californianus), and characterized using a polyphasic taxonomic approach, including sequence analysis of the ribosomal rRNA genes, multiple proteincoding housekeeping genes, genome sequence analysis and phylogeny, and description of their phenotypic features.…”
mentioning
confidence: 99%
“…Recently, GBS has been shown to cause foodborne infection associated with the consumption of raw fish in otherwise healthy adults in Singapore (and likely throughout Southeast Asia) (12)(13)(14). Accordingly, GBS is also well known to colonize and infect (often resulting in severe invasive disease) multiple other species, including fish (where it has a large impact on aquaculture) as well as other mammals, amphibians, and reptiles (15)(16)(17)(18)(19)(20). As an important pathogen of humans, cows, and fish, GBS is therefore of concern for public health, economic, and zoonotic reasons.…”
Section: Introductionmentioning
confidence: 99%